2016
DOI: 10.1089/dna.2016.3360
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Enhances Drug Resistance and Promotes In Vivo Tumor Growth of Lung Cancer Cells

Abstract: Drug resistance is an obstacle in the chemotherapeutic treatment of lung cancers. In the present study, the effects of high-mobility group box 1 (HMGB1) protein in chemotherapeutic resistance and the relationships between HMGB1 and chemotherapy drug-induced cell apoptosis or necrosis were clarified. We used cisplatin-sensitive A549 cells and cisplatin-resistant A549/DDP cells as cell models with IC50 of 11.58 and 46.95 μM, respectively. A549/DDP had higher level of HMGB1 compared with A549 cells. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…About 95% of EAC patients are prescribed cisplatin in the first-line setting ( 3 ). We discovered that seven proteomic expression trends associated with cisplatin resistance were seen to be either overexpressed or downregulated in the vast majority of EAC tumors analyzed in our study—HMGB1, IL-1RA, LGALS3BP, PRMT1, S100A8, SFN, and TXN ( 11 , 12 , 16 , 17 , 20 , 23 , 27 , 28 , 32 , 33 ). About 63% of EAC patients receive the chemotherapy drug 5-FU in the first-line setting ( 3 ).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…About 95% of EAC patients are prescribed cisplatin in the first-line setting ( 3 ). We discovered that seven proteomic expression trends associated with cisplatin resistance were seen to be either overexpressed or downregulated in the vast majority of EAC tumors analyzed in our study—HMGB1, IL-1RA, LGALS3BP, PRMT1, S100A8, SFN, and TXN ( 11 , 12 , 16 , 17 , 20 , 23 , 27 , 28 , 32 , 33 ). About 63% of EAC patients receive the chemotherapy drug 5-FU in the first-line setting ( 3 ).…”
Section: Resultsmentioning
confidence: 76%
“… The table includes the expression difference values between normal and tumor cells, the percentage of patients exhibiting these expression patterns, the descriptions of these markers involvement in other cancerous indications, potential drug types to target these markers, and reported associations to chemoresistance ( 12 , 15 , 16 , 21 , 25 27 , 32 , 34 ). 5-FU, fluorouracil; CRC, colorectal cancer; ESCC, esophageal squamous cell carcinoma; NSCLC, non-small cell lung carcinoma .…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular HMGB1 has a paracrine role, promoting the processing and presentation of tumor antigens by dendritic cells [28,29]. On the other hand, intracellular HMGB1 promotes growth, invasion and resistance of cancer cells to therapy, both in vitro and in vivo [30]. Assessing the TCGA database we found that high levels of HMGB1 are associated with poor prognosis in NSCLC, suggesting that the intracellular role is dominant (Additional file 4: Figure S4).…”
Section: Discussionmentioning
confidence: 94%
“…Extracellular HMGB1 has a paracrine role, promoting the processing and presentation of tumor antigens by dendritic cells [47,48]. On the other hand, intracellular HMGB1 promotes growth, invasion and resistance of cancer cells to therapy, both in vitro and in vivo [49]. Assessing the TCGA database we found that high levels of HMGB1 are associated with poor prognosis in NSCLC, suggesting that the intracellular role is dominant (Additional file 7: Fig.…”
Section: Discussionmentioning
confidence: 96%